The way to become a friend with stress - Rizulla, A. R.; Tashimova, F. S. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2018)
This paper shed a light on the stress phenomenon from the perspective that contrary to lay beliefs about stress as negative phenomenon. The article explores the nature of the stress both in physiological and psychological level. The paper develops the idea about physiological changes that cooccur with stress are not necessarily bad. Much can be done during stressful experiences to promote adaptive responses. Authors conducted analyses of empirical data related to stress investigations obtained by foreign scientists. Stress as any of other phenomenon has negative and positive sides. It may destroy humanity and allow living in prosperity at the same time. The vast majority of research suggest that cognitive appraisals are powerful tools that help shift negative stress states to more ones that are positive. Positive reappraisal improve our performance, coping and physiological state of our body. Moreover, besides stress hormones (i.e. adrenaline and cortisol), stress provokes oxytocin production in our body, which triggers our prosocial behavior and thus, helps us to adapt to the environment and obtain social support. Social support suppress negative outcomes of stress and helps to apply productive coping strategies. By reframing the meaning of the physiological signals that accompany stress, person can benefit physiological reactivity, attention, performance, explore its potential applications, and shift life and its perception from negative to positive. Key words: stress, sympathetic nervous system, reappraisal, emotional and cognitive regulation.